Respostas

2014-02-13T16:37:16-02:00
Sistema de equação:
1) x + y = -5          então   x = (-5 - y)
2) x . y = - 14        substituindo a 1a. na 2a., temos:
 
 (-5 . -y) . y = -14       Dados: { a = 1; b= -5 e c= 14}  Delta = b² - 4a.c
-5y . y² + 14 = 0         Então temos que Delta = (-5)² - 4 . 1 . 14 = 25 - 56 = -31 ???? (Delta inexistente, pois não existe raiz quadrada de número negativo)
                                  f(x) = -b/2a
                                  f(x) = - (-5)/2.1
                                  f(x) = 5/2
f(x) = 2,5